CD4/CD8 Ratios among Blood Donors in Penang - Musa, M; Sidek, R (1990)
In this study, the value for CD4/CD8 (Th/Ts) ratios among blood donors of various ethnic groups in Penang was established. The range ofCD4/CD8 ratio among blood donors in Penang obtained from this study was O. 75-2.13 with the mean of1.36. The significance of biologic variables such as age and race on the ratio was also determined in this study. There was no significant difference for the range of CD4/CD8 ratio between Malays, Chinese and Indians. Likewise, there was also no significant difference for CD4/CD8 ratio in terms of their age.